Governance Unveiled: Jeremy Bentham's Legal Philosophy in Government Policies through the Bantuan Langsung Tunai (BLT) Program for Village Funds - Noorsanti, Inggal Ayu; Yudhanti, Ristina (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2023)
Jeremy Bentham's theory of utility, one of objectives of the law is to provide the maximum benefit to the community. The flow has the principle that humans will take actions to get happines and reduce suffering Benefit Theory can be used as a reference in every policy issued by the Government. Policies must truly provide benefits to the public and not cause harm to society. One of the Indonesian government's policies is Direct Village Fund Cash Assistance to minimize the impact of Coronavirus Disease 2019 (Covid-19) on village communities, then these benefits can be used as a tool to rebuild the welfare of village communities in the economic sector. To solve this problem, the author uses analytical descriptive methods. The results of this research is to indicate that the relevance of the benefit theory initiated by Jeremy Bentham to the Indonesian government's policy of Village Cash Direct Assitance is that if the benefit theory is applied to the policy, it will provide happiness and benefits for the community which will ultimately lead to development. welfare of life, especially village communities who are the target group for the Village Cash Direct Assitance program.